Sprawozdanie z badań pałacu w Ostromecku, gm. Dąbrowa Chełmińska, woj. bydgoskie, w 1981 r. - Grabarczyk, Tadeusz; Kajzer, Leszek; Walenta, Krzysztof (Acta Universitatis Lodziensis. Folia Archaeologica, 1984)
Studies conducted at Ostromecko in 1981 aimed at archaeological verification of the chronology of the "old palace" and examination of the manor mound. The vast park system houses the so-called old palace with its present form given to it by Saxonic architect M. D. Pöppelmann (2nd quarter of 18th century), and the so-called new palace erected in 19th century, most probably according to K. Schinkel's design. As there were discovered archival materials from 17th and 18th centuries containing a description of a defensive manor-house melted in the mass of the "old palace" today, it was decided to examine the foundations of the building and its direct environment. Examinations encompassed four excavations with a total area of 22 m2. It was discovered that on the northern elevation the access to the foundations is covered by walls coming from 18th century remodellings. On the other hand, on the western elevation there were found cut off remnants of the corner abutment from 16th-17th century. It was also observed that the palace foundations were uncovered and mended in 18th century. In excavation IV the mound's stratigraphy was examined, and it was discovered that all older stratifications were removed in 18th century. Scarce historical materials (vessel ceramics, animal bones, tiles, etc.) come from 18th-20th centuries. The studies revealed that remodellings from 18th century and levelling of the mound completely erased the picture of the old foundations.